Work–life conflict and its health effects on Moroccan gastroenterologists: a cross-sectional study - Benayad Aourarh; Tarik Adioui; Sanaa Berrag; Fouad Nejjari; Aziz Aourarh; Mouna Tamzaourte (Therapeutic Advances in Gastroenterology)
Background: Gastroenterologists are exposed to various health-related risks due to their diverse professional roles, including endoscopy, clinical care, and academic responsibilities. Objectives: This study aims to assess the work–life balance (WLB), the prevalence of work-related physical and mental symptoms among gastroenterologists practicing in Morocco, and the effects of WLB on their health. Design: Survey study. Methods: A total of 152 gastroenterologists from various Moroccan cities participated in an anonymous electronic questionnaire regarding their daily activities and symptoms. A WLB ratio was calculated, and musculoskeletal, gastrointestinal, and mental symptoms were recorded. The Maslach Burnout Inventory (MBI) was used to measure the burnout score. Data were analyzed using JAMOVI 2.5 software. The reporting of this study conforms to the Checklist for Reporting Results of Internet E-Surveys (CHERRIES) statement. Results: This study included 152 gastroenterologists (72.4% female; sex ratio = 0.38) with a median age of 31 years (range: 26–64). Among participants, 61.8% were married, and 70.2% were married to physicians. The average working hours were 50.2 ± 12.7 h/week. Health-related symptoms were common: 86.8% reported musculoskeletal disorders, and 71.1% reported digestive disorders. Regarding mental symptoms, 23.7% reported anxiety, and 46.1% reported depression, with 21.1% experiencing both. The median WLB ratio was 0.42 (range: 0.32–0.55). In univariate analysis, the ratio was correlated with age ( p  < 0.001) and mental symptoms (depression, p  < 0.001; anxiety, p  = 0.007). Multivariate analysis revealed age as the only significant associated factor (beta = −0.24 (95% confidence interval: −0.46 to −0.013)). Using the MBI scale, 72.4% of respondents experienced burnout, which correlated with the WLB ratio ( p  = 0.04). In addition, depersonalization (DP) showed a moderate negative correlation with age ( p  = 0.002, r  = −0.32), while personal accomplishment (PA) showed a moderate positive correlation with age ( p  = 0.003, r  = 0.31). Conclusion: Moroccan gastroenterologists suffer from musculoskeletal, digestive, and mental symptoms, and are prone to burnout likely due to long and labor-intensive. Our study found that younger individuals worked more and were more likely to experience burnout, particularly with increased DP toward patients and diminished PA. The mechanisms behind this observation may be linked to higher workloads, less autonomy, and limited coping strategies, factors that should be explored further.